2022
DOI: 10.3390/jcm11164726
|View full text |Cite
|
Sign up to set email alerts
|

A Path Model for Subjective Well-Being during the Second Wave of the COVID-19 Pandemic: A Comparative Study among Polish and Ukrainian University Students

Abstract: Background: Previous studies showed several associations between physical and mental health dimensions and well-being. This study aims to examine a complex path model explaining the life satisfaction of university students from Poland and Ukraine during the second wave of the COVID-19 pandemic. Methods: The cross-sectional web-based study was performed in November 2020 using Google Forms. The conventional sample of 3230 university students from Poland (n = 1581) and Ukraine (n = 1649), aged 18–59 (M = 21.40, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 105 publications
1
6
0
Order By: Relevance
“…The current study aligns with our previous findings [ 6 ], which indicated similar associations between life satisfaction, stress, anxiety, and depression. However, this study extends our previous research by evidencing that anxiety should be treated to the greatest extent in campus prevention and intervention programs.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The current study aligns with our previous findings [ 6 ], which indicated similar associations between life satisfaction, stress, anxiety, and depression. However, this study extends our previous research by evidencing that anxiety should be treated to the greatest extent in campus prevention and intervention programs.…”
Section: Discussionsupporting
confidence: 93%
“…Cross-cultural research showed that university students from Ukraine reported fewer symptoms of stress, PTSD, anxiety, depression, and life dissatisfaction than those from other countries, including Poland, Slovenia, Turkey, Israel, Colombia, or Germany [ 2 – 6 ]. Ukrainian students seem to adapt well to difficulties and are more resilient than university students from many other countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outbreak of the COVID-19 pandemic made it necessary to implement immediate restrictions and physical distancing to control the spread of the virus. The threat of the virus in combination with restrictions and quarantines has been associated with increased rates of anxiety, depression, stress, and decreased well-being [ 1 , 2 , 3 , 4 ]. In parallel, self-reported pain increased [ 5 , 6 , 7 ], especially when patients suffering from chronic pain did not have access to treatment [ 8 ], suggesting that adequate clinical care can prevent pain augmentation during a pandemic [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors found increased levels of stress, anxiety and depression anddecreased life satisfaction and physical health. The authors highlighted that low perceived COVID-19-related stress directly influenced life satisfaction and anxiety level [ 5 ].…”
mentioning
confidence: 99%